Strategi Dinas Pemberdayaan Masyarakat dan Desa dalam Pelaksanaan Program Kampung KB di Desa Lipukasi Kecamatan Tanete Rilau Kabupaten Barru - Asrar, M Asrar; Parawangi, Anwar; Azikin, Ruskin (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study aimed to find out how the KB village Kampung Program Implementation Strategy in The Lipukasi Village, Tanete Rilau District, Barru Regency. This study used a qualitative descriptive research method system. Data collection techniques were observation, interview and documentation. While data analysis used data reduction, data presentation and drawing conclusions. The result of this study showed that The Strategy in Implementing the KB Village Program in Lipukasi Village, Tanete Rilau District, Barru Regency had been running quite well, this could be seen with the number of KB village programs that had been implemented. However, constraints occurred in the Implementation such as community participation, budget and communication of each agency was still not optimal. This happened because of the lack of communication between agencies as well as the lack of cooperation between Implementers and related agencies which caused constrained activities